2020
DOI: 10.1155/2020/6161536
|View full text |Cite
|
Sign up to set email alerts
|

Dysmenorrhea and Associated Factors among Polish Women: A Cross-Sectional Study

Abstract: Purpose. The aim of the research was to conduct an assessment of the prevalence of dysmenorrhea and associated factors among Polish women. Patients and Methods. A cross-sectional study was conducted among Polish women using an online questionnaire. The mean age of the participants was 23 ± 4 years. Out of the total of 1,317 women who took part in the study, 1,127 were included in the analysis, and 190 were excluded due to incomplete answers. The que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
(56 reference statements)
1
24
0
5
Order By: Relevance
“…Previous research has demonstrated that dysmenorrhea is a complex process that depends on various factors [1][2][3]. Both our study and research conducted by other authors have shown that the following factors may have an impact on the development of dysmenorrhea: genetic causes, including the condition diagnosed in the mother and sisters, premenstrual syndrome (PMS), early age of menarche, stressful lifestyle, the lack of physical activity, loss of weight, unhealthy habits, social problems, depression, and even low self-esteem [4][5][6][7]. Other authors have demonstrated that hormones, particularly increased secretion of prostaglandins, may cause dysmenorrhea [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that dysmenorrhea is a complex process that depends on various factors [1][2][3]. Both our study and research conducted by other authors have shown that the following factors may have an impact on the development of dysmenorrhea: genetic causes, including the condition diagnosed in the mother and sisters, premenstrual syndrome (PMS), early age of menarche, stressful lifestyle, the lack of physical activity, loss of weight, unhealthy habits, social problems, depression, and even low self-esteem [4][5][6][7]. Other authors have demonstrated that hormones, particularly increased secretion of prostaglandins, may cause dysmenorrhea [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Hasil ini didukung oleh penelitian bahwa klasifikasi dismenorea pada responden mayoritas adalah dismenorea ringan (49,4%). Penelitian Barcikowska (2020) juga menemukan bahwa kejadian dismenorea pada responden sebanyak 94%. Dismenorea ringan merupakan rasa nyeri yang berlangsung beberapa saat sehingga perlu istirahat sejenak untuk menghilangkan nyeri tanpa disertai pemakaian obat.…”
Section: Pembahasanunclassified
“…Peneliti Vlachou (2019) juga menunjukkan bahwa tidak ada perbedaan yang signifikan pada merokok, olahraga, body mass index (BMI) dan durasi siklus menstruasi pada kelompok nyeri ringan, nyeri sedang, nyeri berat, dan tanpa nyeri (p> 0,1). Penelitian Barcikowska (2020) ada hubungan yang signifikan antara IMT dan Dismenorea (p=0,271). Status gizi underweight dan overweight jika dibandingkan dengan status gizi normal, hasilnya tidak ada hubungan yang bermakna antara status gizi dengan dismenorea (Sirait, 2014).…”
Section: Pembahasanunclassified
“…Prostaglandins produced by the linings of the uterus have been identified as one of the reasons for the pain since it is known to cause abnormal contractile activity leading to ischemia and hypoxia of the uterus and hence increased sensitivity of the nerve endings [6]. Nonsteroid anti-inflammatory drugs (NSAIDs) are recognized as the first-line treatment in dysmenorrhea [7], though 25 to 30% failure normally reported [8]. At the menopausal phase, women experience physiologic deterioration of hypothalamic-pituitary-ovarian axis function resulting in hormonal imbalance and a variety of symptoms such as hot flushes, sweating, sleep disturbance, mood swings, depression, cognitive decline, vaginal dryness and sexual dysfunction occur with a significant impact on their quality of life [9,10].…”
Section: Introductionmentioning
confidence: 99%